Inhomogeneous superconducting phases in the frustrated Kondo-Heisenberg chain - Dobry, Ariel Oscar (2013)
We use bosonization and renormalization group methods to determine the ground-state phase diagram of a one-dimensional frustrated Kondo-Heisenberg system consisting of a one-dimensional spin- 1/2 Luttinger liquid coupled by a Kondo exchange interaction J K to a frustrated quantum antiferromagnetic Heisenberg chain, with a nearest-neighbor exchange coupling J1 and a next-nearest-neighbor (frustrating) exchange interaction J2. We analyze the interplay of quantum frustration in the antiferromagnetic chain with the Kondo exchange coupling J K with the Luttinger liquid. We discuss the structure of the phase diagram of this system as a function of the ratios J K/J1, J2/J1, and of the parameters of the Luttinger liquid. In particular, we discuss in detail the regimes in which a pair-density-wave state may be realized and its relation with the spin correlations in the frustrated antiferromagnetic chain.